Verification of the Efficiency of Alternative Furrow Irrigation on Water Productivity and Onion Yield at Woleh Irrigation Scheme, Northern Ethiopia - Abera, messay; Wale, Aemro (International Journal on Food, Agriculture and Natural Resources, 2024)
In the semi-arid regions of Ethiopia, water is the most limiting factor for crop production. Meeting crop water demand maximizes productivity from a land unit but does not inherently increase revenue per unit of water. This has led to a growing interest in irrigation practices that improve water productivity by regulating the inappropriate use of irrigation water. The experiment was conducted in the Woleh irrigation Scheme, to verify the efficiency of alternative furrow irrigation on onion water productivity and yield. The treatments used a randomized complete block design with four replications. Alternating furrow irrigation (AFI), conventional furrow irrigation (CFI), and fixed furrow irrigation (FFI). Each method used 75% ETc of the irrigation water. The experiment showed that AFI had the highest yield and water productivity. The amount of irrigation water used for AFI and FFI was about half (3038 m3) of CFI (6078 m3). The water productivity obtained was 4.05 kg m-3 for AFI and 3.16 kg m-3 for FFI, almost double the 2.15 kg m-3 for CFI. Economic water productivity and marginal rate of return were greatest in AFI. Therefore AFI at 75% ETc was superior in yield and water productivity in areas with water scarcity and high labor costs.